SOSIALISASI PERHITUNGAN ZAKAT BERDASARKAN PERATURAN MENTERI AGAMA NO. 52 TAHUN 2014 DAN MODEL PENYALURANNYA DI PONDOK PESANTREN ARRAHMAN - Niswatin Mubarriroh; Nur Izzah; Hendra Kholid (DEVELOPMENT: Journal of Community Engagement, 2022)
This community service activity aims to improve the understanding and implementation of zakat calculation according to the Minister of Religious Affairs Regulation (PMA) No. 52 of 2014 and to develop an effective zakat distribution model at the Arrahman Islamic Boarding School in Cidadap, Serang, Banten. The identified problem was a lack of in-depth understanding among the school's administrators regarding contemporary zakat calculation standards, as well as a suboptimal distribution model that had yet to sustainably empower beneficiaries (mustahik). The method used was a participatory approach through socialization, training, and Focus Group Discussions (FGD). The results of the activity showed a significant increase in the administrators' knowledge and skills in calculating zakat correctly, as evidenced by the increase in the average post-test score to 80 from an initial 55. Furthermore, a hybrid distribution model was successfully formulated, combining consumptive aid for urgent needs with productive programs aimed at empowerment. This program is expected to enhance the accountability of zakat management and maximize its positive impact on community welfare.